Left atrial appendage velocity as an instrument of predicting atrial fibrillation recurrence after successful catheter ablation – a useful tool?. (14th October 2021) - Grade Santos, J; Budzak, K; Simoes, J; Martinho, M; Ferreira, B; Briosa, A; Pereira, A R; Cruz, I; Almeida, A R; Fazendas, P; Joao, I; Almeida, S; et al.
Abstract: Introduction: Catheter ablation for the treatment of Atrial Fibrillation (AF) is a modality of treatment in growing expansion. However the sustained long term response in preventing AF recurrence is poor for most patients, namely in those with a dilated left atrium. Purpose: Our aim was to assess the utility of an echocardiographic parameter for left atrium function, the left atrial appendage velocity (LAAV), in predicting recurrences after catheter ablation. Methods: We performed a 9 year retrospective analysis of all patients who underwent a successful catheter ablation for the treatment of atrial fibrillation and had a valid pre-procedural transesophagic echocardiogram in a single expert centre. Medical records were analysed for demographic, procedural data and outcomes. Results: Seventy-three (73) patients fulfilled all inclusion criteria and were analysed. The mean age was 62±11 with a male preponderance (58, 7%). The majority of patients (82, 7%) had preserved left ventricle ejection fraction. Only 46% of patient had a volumetric assessment of the left atrium dimensions prior to ablation, with slight, moderate and severe dilation of the left atrium in 20%; 8, 6% and 28, 6% of patients. Of the patients subjected to an AF ablation the average LAAV was 50, 6±19 cm/s, with 78% of patients with normal atrial appendage velocities. Patients with low LAAV (<40cm/s) had a higher proportion of AF recurrences at 3 and 6 months (58, 3 vs 12, 8% and 89% vs 21, 7%; p<0, 05 for all) with a linear correlation between the presence of recurrences and LAAV (LAAV of 39, 1 vs 57, 5 cm/s; p<0, 05 OR 0, 91 (CI 95% = 0, 85–0, 97); r2=0, 34 at 3 months and LAAV of 43, 5 vs 59 cm/s; p=0, 01; OR 0, 94 (CI 95% = 0, 89–0, 99); r2=0, 24 at 6 months respectively). There was a trend towards association with recurrences at 1 year although it did not reach statistical significance. There was no significant difference in the use of antiarritmic drugs, either prior or post ablation, in both groups. It was not possible to assess the additive predictive value to the left atrium dimensions due to the low percentage of volumetric assessment of left atrium prior to AF ablation. Conclusions: Patients with low left atrial appendage velocities had a lower long term success rate of catheter ablation, with higher rates of recurrence at 3 and 6 months and a trend towards higher recurrences at 1 year, with linear correlation which hypothesises the use of the left atrial appendage velocity as novel predictive parameter for an integrative model. Funding Acknowledgement: Type of funding sources: None.